Modelling of Flavanoid Derivatives from Leucaena leucocephala as Anti-UV - Rokiy Alfanaar; Tety Wahyuningsih Manurung; Mokhamat Ariefin (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
While UV light has benefits for life, excessive exposure to UV light also has negative effects on humans. Examples of the negative effects of UV exposure include cancer. Therefore, the exploration for materials that can be used as anti-UV continues to grow. One of them is extract from Leucaena leucocephala leaves. To study the potential of a compound as anti-UV, one method can use a molecular modeling approach using the semi-empirical method. Based on this, 8 flavone-derived compounds contained in L. leucocephala leaf extract were modeled with a semi-empirical approach using the PM3 method, and electronic-transition was calculated using ZINDO/S. The geometry optimization results showed that the bond length between carbon atoms in flavonoid tururnans did not change significantly with the difference in functional groups. However, there is a significant difference in the dihedral angle of the compound due to the repulsion of functional groups. The results of the electronic transition calculation showed that all flavonoid derivatives 1-8 are active in the UV A, UV B, and UV C regions. So it can be said that flavones 1-8 have potential as anti-UV. In addition, the energy level of HOMO-LUMO compounds was also calculated. Flavonoid 1 has the smallest Eg while flavonoid 8 has the largest Eg